Wearing Time, Quality of Life, and Complications of Lower Limb Bone-anchored Prostheses: A Systematic Review and Meta-analysis - Clara Thouvenin, MD; Hugo Pelet, MD; Rémi Klotz, MD; Mathilde Puges, MD; Carole Vignals, MD; Thierry Fabre, PhD; Anaïs Delgove, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. This study aimed to assess prosthesis wearing time, quality of life, and complications in patients with lower limb amputations and bone-anchored prostheses (BAPs). Methods:. We searched databases for studies that reported prosthesis wear times and/or quality of life derived using the Questionnaire for Persons with a Transfemoral Amputation score and complications associated with BAPs in patients with lower limb amputations who were followed up for at least 1 year. The results are reported using an aggregative method. We calculated weighted means of functional scores and proportions of complications. Results:. Twelve studies with 414 subjects met the inclusion criteria, but use of the Effective Public Health Practice Project criteria indicated that the methodological qualities were low. The mean prosthesis wearing time before osseointegration was 51% (range 0–100), 83.8% (4.2–100) at 1 year, and 87% (0–100) at the last follow-up. The mean Questionnaire for TransFemoral Amputees Global Score preosseointegration was 38.2 (0–66.7), 71.2 (33.4–100) at 1 year, and 76 (17–100) at the last follow-up. The mean infection rate was 47.5% (0%–94.44%), and the mean extent of septic loosening was 4.6% (0%–27.8%). The mean equipment breakage rate was 26.6% (0%–72.2%), and the mean all-cause implant removal rate was 7.2% (0%–27.8%). Conclusions:. BAPs increased the prosthesis wearing time and the quality of life of patients with lower limb amputations. The results were good after 1 year and were maintained over time. There were many complications, but these did not seem to affect the functional results.